Hubungan Antara Tingkat Pengetahuan Siswa Tentang HIV/AIDS Terhadap Perilaku Seksual Di SMA Cokroaminoto Tamalanrea Makassar Tahun 2022 - Hartati S (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the relationship between the level of students' knowledge of HIV / AIDS on sexual behavior in high school Cokroaminoto Makassar Tamalanrea 2022. Research Methodology This type of research is analytic survey with cross sectional design. This research was conducted in SMA Cokroaminoto Tamalanrea Makassar. The number of samples in this study were 64 respondents. The sample selection using accidental sampling using a questionnaire which serve as the primary data source. The results of this study indicate that disrtribusi frequency of the level of students' knowledge about HIV / AIDS with sexual behavior can be seen that out of 64 respondents, students who have sufficient knowledge and good behavior as much as 23 respondents (95.8%), compared to students who have a level of knowledge sufficient and less behavior there is 1 respondent (4.2%), while students who have less knowledge and good conduct as many as 39 respondents (97.5%), compared to students who have a level of knowledge is less and less that 1 respondent behavior (2 , 5%). Conclusions Most of level of knowledge of students in high school Cokroaminoto Tamalanrea Makassar in the unfavorable category (62.5%) and sexual behavior of adolescents included in either category (96.9%)..